Exterior of the Mulaprasada (main shrine) of the Mahanaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The Mahanaleshwar Temple has a pancharatha (consisting of five projections) plan, meaning that it consists of a main central broad projection that is flanked by an intermediate and corner projection respectively. In elevation, the temple consists of two main components, the vedibandha (basal mouldings) and the jangha (wall) of the temple. The vedibandha is mainly a set of horizontally running mouldings of different forms. The jangha is the primary wall of the temple. At the vedibandha level, the projections of the temple are not separated by recesses called the salilantaras. But the jangha has recesses. Also, the jangha has icons in all the projections and recesses, but the vedibandha is sparsely ornamented. Only the kumbha (pot) moulding of the vedibandha has framed images of deities.